2020
DOI: 10.3390/s20061784
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitive Biosensors Based on the Coupling Between Surface Plasmon Polaritons on Titanium Nitride and a Planar Waveguide Mode

Abstract: High sensitivity biosensors based on the coupling of surface plasmon polaritons on titanium nitride (TiN) and a planar waveguide mode were built; they were proved by sensing three different media: air, water and dried egg white; sensors described here could be useful for sensing materials with a refractive index between 1.0 and 1.6; in particular, materials of biological interest with a refractive index in the range 1.3–1.6, like those containing biotin and/or streptavidin. They were built by depositing Nb2O5/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The dip in the reflectance spectra, shown in Figure a, relates to the excitation of SPPs at the TiN/air interface. , The calculated reflectance spectrum is in good agreement with the experimental responses as shown in Figure a. The broadening in all the spectra is very common and it can be attributed to the low carrier mobility (electrons) due to the larger absorptivity of TiN films than conventional plasmonic materials such as Au and Ag . A slight mismatch between the calculated and experimentally acquired spectra can be understood as follows: a 2 nm seed layer of Cr 90 Ru 10 is used to fabricate TiN thin films suitable for reflectance measurements.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The dip in the reflectance spectra, shown in Figure a, relates to the excitation of SPPs at the TiN/air interface. , The calculated reflectance spectrum is in good agreement with the experimental responses as shown in Figure a. The broadening in all the spectra is very common and it can be attributed to the low carrier mobility (electrons) due to the larger absorptivity of TiN films than conventional plasmonic materials such as Au and Ag . A slight mismatch between the calculated and experimentally acquired spectra can be understood as follows: a 2 nm seed layer of Cr 90 Ru 10 is used to fabricate TiN thin films suitable for reflectance measurements.…”
Section: Resultsmentioning
confidence: 57%
“…The broadening in all the spectra is very common and it can be attributed to the low carrier mobility (electrons) due to the larger absorptivity of TiN films than conventional plasmonic materials such as Au and Ag. 66 A slight mismatch between the calculated and experimentally acquired spectra can be understood as follows: a 2 nm seed layer of Cr 90 Ru 10 is used to fabricate TiN thin films suitable for reflectance measurements. As Cr 90 Ru 10 is optically absorptive, it may cause such a discrepancy and distort some of the coupling capabilities of TiN.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced fluorescence was due to the transfer of photo-generated carriers through carrier diffusion, as well as the trap and electron conductor effects of TiN. Owing to the existence of surface plasmons in the surface state of the TiN NPs, [29,55] the hot electrons of the higher E C of the CsPbBr 3 QDs with higher E C were directly swept and transferred to the E C in the defect state of the ZnO film. Only a small fraction of the electrons fell and recombined with holes.…”
Section: Surface Characteristics Of Tin/zno Heterojunctionmentioning
confidence: 99%
“…In the works [12][13][14], the improvement of sensitivity of SPR-based sensors was under intensive investigation. In [12], the authors used gold nanowires (AuNW) in order to increase the sensitivity of LSPR-based optical fiber refractive index sensor and optimized its parameters.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…Production of a large-area MoS 2 monolayer helped to limit oxidation of silver film and, as the authors demonstrated theoretically and experimentally, served to improve the sensitivity of SPR sensor [13]. In the work [14], the authors built up and investigated characteristics, primarily sensitivity, of SPR-based sensors constructed via deposition of multilayer (Nb 2 O 5 /SiO 2 /TiN) structures on the flat surface of D-shaped prism.…”
Section: Summary Of the Special Issuementioning
confidence: 99%